Oral Haemangioma - Jaspreet Singh Gill; Sharanjeet Gill; Amit Bhardwaj; Harpreet Singh Grover (Case Reports in Medicine)
Vascular anomalies comprise a widely heterogeneous group of tumours and malformations. Haemangioma is the most common benign tumour of vascular origin of the head and neck region. The possible sites of occurrence in oral cavity are lips, tongue, buccal mucosa, and palate. Despite its benign origin and behaviour, it is always of clinical importance to the dental profession and requires appropriate management. This case study reports a rare case of capillary haemangioma on the palatal gingiva in a 14-year-old female.